The Quality of Working Life: a survey among english teachers - Kanikadan, Andréa Yumi Sugishita; Limongi-França, Ana Cristina (Review of Business Management, 2007)
The aim of this research was to study the perceptions of the quality of working life in the English teachers´ occupation. It was adopted two approaches as a theoretical referential for the quality of working life evaluation: the competency and the biopsychosocial approach. The organizational environment considering a language course, the business strategies and the professional profile were also explained in this paper. For data collection it was used a survey on a non-probabilistic sample of 91 English teachers. The purpose of a survey is to collect data considering the characteristics, actions and opinions of a group, using a questionnaire. The results showed that these professionals understand the quality of working life positively. On the other hand, they were concerned about the lack of strategies at the management level. In the long run it might cause damages in health and in the education process if the career management will not be considered as strategic. Key-words: Quality of working life management. Human resources management. Work conditions. English teachers.